PENGARUH KOMPENSASI DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI PADA PT. PELABUHAN INDONESIA I (PERSERO) MEDAN - Ferry Safriandi; Windy Aginta (JURIKOM (Jurnal Riset Komputer), 2016)
Compensation is everything received by employees as remuneration for their work. Discipline is an attitude of willingness to work and one's willingness to adhere to and comply with regulatory norms prevailing around it. Based on these descriptions, the formulation of the problem in this research is how the influence of compensation and working discipline to employee performance at PT. Pelabuhan Indonesia I (Persero) Medan. The theory used in this research is the theory of human resource management-related compensation, discipline of work and employee performance therein including the understanding, the importance, the factors that affect the benefits and objectives and indicators that affect the variable compensation, work discipline and the performance of employees.The research method that I use in this study is a quantitative or qualitative. This type of research is descriptive quantitative nature of the research is associative, data collection methods used were interviews, questionnaires, observation and documentation. The population in the study of more than 200 employees and a sample obtained by using the formula slovin amounted to 67 employees. Data processing using software SPSS 23. Data analysis technique that used were multiple linear regression, test the coefficient of determination (R2), partial test (t test), simultaneous test (F test).The results obtained by the regression equation Y = 0.910 + 0.747 X1 + 0.259 X2 so that the compensation and discipline can improve employee performance. Results obtained determination coefficient R value (R-Square) of 0.508, or 50.8%, this indicates that compensation and disciplinary effect on the performance of employees amounted to 50.8%, the rest is influenced by other variables not examined by the author. F test results obtained F count> F table (33.001> 3.14), it can be concluded that the compensation and working discipline simultaneously affect the performance of employees. T test results obtained for compensation tcount> t table (8.063> 1.99) This means that the hypothesis is rejected. It can be concluded that the compensation partially affect performance, and the t test results obtained for the work discipline tcount> t table (2.304> 1.99) This means that the hypothesis is rejected. So we can conclude that the discipline of work partially affect the performance.He conclusion of this study is that there is the influence of compensation and working discipline to employee performance, either simultaneously or partially on PT. Pelabuhan Indonesia I (Persero) Medan. Keywords: Compensation, Discipline Work, Employee Performance